EFFECT OF DIFFERENT TEMPERATURE AND EXPOSURE TIME ON THE KHAPRA BEETLE Trogoderma granarium Everts (COLEOPTERA : DERMESTIDAE). - Abbas , Tareq S.; Qader, Fadil A. (Diyala Agricultural Sciences Journal, 2016)
This study included the influence of different temperatures 30 , 35 , 40 , 45 ,50, 55 C° and 14 exposure periods 5 ,10 , 15 ,20 , 25 ,30 , 35 , 40 , 45 , 50 , 55 , 60 , 65 , 70 minutes in order to compare with 30 C° , it was found that 30 and 35 C° were suitable for developments of the caterpillar larva instars (first or third and fifth) pupal and survival of adults , the results showed that exposure to 50 C° for all exposure periods was the lethal temperature for all developmental stages , the highest of lethal percent of larval pupal , and adult stages was 100% while the lowest was 0% at 30 and 35Co.